PLANTAIN THEORY AND THE ATTAINMENT OF SDGs 2030 BY AFRICAN STATES: AN EXPOSITION - Frank, Etim O.; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2021)
Agenda 2030 is the Sustainable Development Goals with 17 indicators. Like its predecessors, Millennium Development Goals (MDGs),with only eight goals yet African states could not achieve half of the eight goals then and may not get close to a quarter of the SDGs because of the pathologies of development which are legendary in Africa. This study evaluated the feasibility of using the Plantain tree crop, in which many African countries have global comparative advantage as a means to attaining seven or 41.17 per cent of the 17 goals, against one-fit-all approach often applied to such development agenda. The method of study was descriptive which through its procedure revealed, that these countries were not putting this crop and its properties to optimum usage. This approach was complemented by observations and triangulation by library researches on the various usages of plantain tree. The technique included informal interviews of traditional medicine practitioners on the ailments cured through the use of plantain properties. The tactic of the study further revealed that the life-span of plantain is about 20 years, hence it can feed the present and future generation, it withstands every climatic condition, and the fruit could be eaten ripe, unripe, as chips, as plantain four and paste use in pharmaceutical industries for drugs making. Every part of the plantain tree is use by alternative medicine practitioners. It resolved that the countries that have global comparative advantage with plantain, could harness all the economic and medicinal advantages to achieve the SDGs by 2030 without having to borrow, being already heavily indebted nations. Political will and leadership and investments are some of the requirements needed to achieve the goals pursue herein. This affirmed the efficacy of Plantain theory as mechanism to achieving some per cent of the SDGs by some African States.